THE EFFECT OF MODEL PROBLEM BASED LEARNING ON LEARNING OUTCOMES OF STUDENT IN GRADE VII AT SMPN 7 SIJUNJUNG - Hanifah, Hayatul Hani; Arif, Khairil; Yanto, Febri; Sari, Monica Prima (Department of Science Education, 2025)
Kurikulum Merdeka expects students to be able to develop soft skills and character in accordance with the Pancasila Student Profile. One of the lessons that can realize the Pancasila Student Profile is science. Implementing of science learning in schools requires a learning model so that the learning process has systematic step. One of the learning models recommended are Problem Based Learning (PBL) model. This type of research is quasi experiment with posttest only control group design. The population in this study were all student in VII grade at SMPN 7 Sijunjung. This experiment using purposive sampling technique, so that the sample were obtained as student at class VII. 5 and VII. 6. The research sample consisted of one experimental class applying the Problem Based Learning assisted by practicum and the control class using the conventional learning model. The research result obtained an average of experimental class = 49,97 and control class = 45,33. Based on prerequisite test, it was found the data were normal and homogenous. Include that the data on research show a significant influence in application of the Problem Based Learning on student in grade VII at SMPN 7 Sijunjung.